NEW MEDIA-OLD LANGUAGE: SEXIST DISCOURSE IN THE COLLABORATIVE ONLINE DICTIONARIES - Sibel Fügan VAROL (Fırat University, 2019)
Online dictionaries built up on user contribution are one of the platforms provided by the new media, unlike traditional mass media, to the audience. Such dictionaries with a potential to provide a free and alternative public discussion platform have become a sort of platform influential on the shaping of cyber culture by virtue of the meanings they attribute to concepts and the values they transmit to the public. Analysis of such medium with various aspects would contribute significantly to the accumulated knowledge on cyberculture, which is one of the most important categories of new media studies. In this paper seeking to provide such contribution by interrogating the sexist discourse in these sites, 11 online dictionaries of this kind were determined by entering the keywords “woman” and “dictionary” in Google in the first instance. Thereafter, a content analysis was carried out in such 11 online dictionaries entering the keyword “woman” in each site to determine the attitude of the entry authors towards women, the characteristics used most frequently to identify women and whether a hate speech was used in the online dictionaries. The analysis has revealed that a sexist discourse dominated the dictionaries analysed hereunder, that through the pornographic statements about women, the dictionaries contributed to the construction of the image of women in the collective mind of the society as a sexual object, thereby instrumentalizing women in a discourse of hatred. The overall finding of the research is that the online dictionaries adopt an attitude maintaining and reinforcing the current sexist social structure, rather than providing a new and alternative discussion platform.